2018
DOI: 10.1002/solr.201800147
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable Semi‐Transparent p‐i‐n Planar Perovskite Solar Cells by Atmospheric Pressure Spatial Atomic Layer Deposited ZnO

Abstract: The replacement of the conventional top metal contact with a semi‐transparent conducting electrode such as sputtered indium‐tin oxide (ITO) is strictly required to adopt the perovskite solar cell (PSC) in hybrid tandem photovoltaic applications. In order to prevent sputtering damages on the perovskite absorber and the organic materials adopted in p‐i‐n planar architecture, an atmospheric pressure spatial atomic layer deposited (s‐ALD) ZnO buffer layer has been included. The use of a 45 nm thick s‐ALD layer ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Moreover, they can also act as excellent barriers to prevent damages induced by metal diffusion and outside moisture and inside halogen. [248][249][250][251][252][253][254] However, proper buffer layers are required to protect the under layers when sputter ITO or (indium zinc oxide) IZO as electrodes in semitransparent PSCs and tandem PSCs due to the strong power of sputtering. Boyd et al deposited an impermeable ITO layer on the top of PCBM layer.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they can also act as excellent barriers to prevent damages induced by metal diffusion and outside moisture and inside halogen. [248][249][250][251][252][253][254] However, proper buffer layers are required to protect the under layers when sputter ITO or (indium zinc oxide) IZO as electrodes in semitransparent PSCs and tandem PSCs due to the strong power of sputtering. Boyd et al deposited an impermeable ITO layer on the top of PCBM layer.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 99%
“…[251] The compact ALD-oxides are also recognized as advantageous buffer layers for sputtering transparent electrodes. [252][253][254][255] Najafi et al fabricated semi-transparent PSCs with the TCO/ NiO/perovskite/PCBM/np-ZnO/ALD-AZO/ITO structure. [238] The unencapsulated PSCs retained ≈90% of the initial PCE after the storage of 20 months in dark and showed only 4% degradation after tracking at MPP for 1500 h at 65 °C in the N 2 -filled atmosphere glove box.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high throughput characteristic of SALD is of high relevance for organic-based PV technology. Recently, it has also been shown that SnO x and ZnO films deposited by SALD can have a beneficial impact on the stability of hybrid perovskite solar cells [62,69].…”
Section: Taking Advantage Of Saldmentioning
confidence: 99%
“…Intrinsic metal oxides HfO 2 [11] Al 2 O 3 [14-16, 19-21, 26, 31, 35-50] ZnO [18,36,39,45,46,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] SnO x [68,69] TiO 2 [14,18,[70][71][72] Cu 2 O [46,73,74] Nb 2 O 5 [71] NiO x [91] ZrO 2 [92,93] MoO x [94] Doped SALD has also been used for LEDs, in some cases to deposit active ZnO layers for polymer and hybrid perovskite-based diodes [54,76], and in another case using Al 2 O 3 as permeation barrier for flexible organic LEDs [49]. Other authors have also demonstrated the suitability of SALD for depositing barrier and encapsulation layers both on plastic and paper substrates [14,31,40,48].…”
Section: Materials Referencesmentioning
confidence: 99%